ANALISIS PENTINGNYA KESADARAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI PERUSAHAAN TEKSTIL - Rizky Bagus Setyajj; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
Low company and employee awareness of occupational safety and health (K3) can have a crucial impact in the form of work-related accidents and occupational diseases. The purpose of this study was to determine the level of OSH awareness by employees at Textile Company, knows the impact of the attitude of employees who ignore the important of K3 awareness, and knows the efforts of the company and employees in preventing work accident. This research is a qualitative research with a case study approach. The data sources for this research were obtained directly from employee work activities, interviews with section heads, shift heads, office staff, 4 employees and documents in the form of employess attendance data, company administration data, machine data, equipment data, materials data, and accident health data. Work, the sampling technique was carried out by means of purposive sampling. Meanwhile, data collection was carried out using interview techniques, observation and document study. The data analysis technique used is source triangulation and methode triangulation. The data analysis technique used is the interactive data analysis model of Miles and Huberman which consist of data reduction stages, presenting data, and making conclusions. Furthermore, the results of the study show that the level of employee awareness of occupational safety and health is seen from several aspects, namely the use machine, tools, materials, and working environment conditions, work methods, work position, and employee lifting loads, interpersonal relationship, roles and responsibilities towards work, as well as hygiene facilities that are clean and healthy. The impact of the low level of company and employee awareness of K3 can cause work-related accidents and occupational diseases which are divide into 3 causal factors, namely technical factors, non-technical factors, and natural factors. Efforts made by companies and employees in preventing work accident are efforts to prevent work accidents using hazard control in workplace, prevention efforts through guidance and supervision, and prevention efforts through management systems.